2013
DOI: 10.1016/s1514-0326(13)60007-0
|View full text |Cite
|
Sign up to set email alerts
|

Inequality, Aid and Growth: Macroeconomic Impact of Aid Grants and Loans in Latin America and the Caribbean

Abstract: would like to thank Rogelio Madrueño, Rafael Domínguez and two anonymous referees for their comments and suggestions. We also gratefully acknowledge the financial support of the Spanish Aid Agency (AECID). The views expressed in this paper, however, remain solely those of the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…This could be construed as aid becoming neutral in the long term. The long‐run aggregate effects of aid could be more apparent when inequalities are dealt with (Tezanos et al ., , p. 153) . Within the context of this essay, there are three main motivations for using inequality as a benchmark for foreign aid: provide incentives for recipient governments to reduce inequality and hence, improve governance; remain consistent with Piketty and prepare for the post‐2015 agenda of sustainable development.…”
Section: Introductionmentioning
confidence: 97%
“…This could be construed as aid becoming neutral in the long term. The long‐run aggregate effects of aid could be more apparent when inequalities are dealt with (Tezanos et al ., , p. 153) . Within the context of this essay, there are three main motivations for using inequality as a benchmark for foreign aid: provide incentives for recipient governments to reduce inequality and hence, improve governance; remain consistent with Piketty and prepare for the post‐2015 agenda of sustainable development.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, we have developed an analytical framework accounting for these two aid modalities: aid grants and aid loans. As previously argued by Chang et al (2002) and Tezanos et al (2013), such a model disentangling overall ODA in these two components should give deeper insight into the existence of perverse aid effects and the extent to which they undermine the potential of aid to boost and sustain growth.…”
Section: A Analytical Frameworkmentioning
confidence: 82%
“…Elsewhere, Tezanos et al (2013) distinguished between two aid modalities (aid loans and aid grants) in Latin America and the Caribbean (LAC) countries, and concluded that the impact of loans was greater than the impact of grants, a result that -according to the authors-supports the use of both aid modalities in a middle-income region such as LAC, despite its long record of debt unsustainability problems.…”
Section: A Analytical Frameworkmentioning
confidence: 99%
“…Furthermore, the studies of Ouattara and Strobl (2008) and Annen and Kosempel (2009) evaluated the effectiveness of "technical assistance", assuming that this type of aid stimulates human capital accumulation by facilitating knowledge transfer; nonetheless, these two studies achieved opposite results: the first one claimed the ineffectiveness of this aid, and the second asserted its effectiveness. Finally, Tezanos et al (2012) studied the effectiveness of aid grants and aid loans in Latin America and the Caribbean, suggesting that both were economically and statistically significant, although the estimated growth impact of concessional loans was greater than the impact of grants.…”
Section: Recent Studies On Aggregate Aid Effectivenessmentioning
confidence: 99%